Duodenal Eosinophilia in Functional Dyspepsia - A. S. Silaeva; E. L. Bueverova; Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present observation of a patient diagnosed with functional dyspepsia based on current guidelines, and having increased eosinophil counts in the biopsy specimen of duodenal mucosa. To consider possible causes of duodenal eosinophilia in the light of present-day concepts.Highlights. Patient K., 40 years old, complained of dyspeptic phenomena, the first appearance of which she had noted at the age of 18. The patient noted poor tolerance to canned and fermented foods, which provoked an increase in dyspepsia and sometimes caused watery diarrhea. The examination excluded “symptoms of concern”. Successful antihelicobacter eradication therapy was carried out. Morphological examination of the stomach showed phenomena of mild chronic inflammation without intestinal metaplasia or glandular atrophy. A biopsy of the mucosa of the descending part of the duodenum showed a moderate increase in the levels of mononuclears and eosinophils in its lamina propria without penetration into the epithelium of the villi or formation of clusters. The patient suffers from pollinosis; sensitization to birch pollen was diagnosed by a skin prick test. However, she has no oral allergy symptoms, which does not allow linking duodenal eosinophilia to food allergy. Based on current guidelines, the patient was diagnosed with functional dyspepsia. In addition to dietary restrictions, treatment courses with a proton pump inhibitor, itopride, and S-methylmethionine sulfonium chloride, which has an antihistamine effect, were recommended for periods of worsening dyspepsia.Conclusion. The clinical significance of duodenal eosinophilia and local histamine production in patients with a clinical diagnosis of functional dyspepsia deserves special attention. Triggering factors provoking the worsening of symptoms should be analyzed; in particular, a food diary and exclusion of food allergies are recommended. Histamine-neutralizing drugs may play a role in the treatment of FD with duodenal eosinophilia in the future.